Evaluation of Antifungal Properties Against the Phytopathogenic Fungus Botrytis Cinerea of Anthocyanin Rich-Extracts Obtained from Grape Pomaces - Cotoras-Tadic, M; Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Aguirre-Quintana, M; Aguirre-Quintana, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Vivanco-Millares, M; Vivanco-Millares, M (Sociedad Chilena de Quimica, 2013)
The anthocyanin content of grape pomace from different Chilean grape varieties (Vitis vinifera var. Cabernet Sauvignon, Carménère and Syrah) from two vineyards (Misiones de Rengo and Miguel Torres) was determined by the differential pH method and the anthocyanin perfile was characterized by HPLC. In all chromatograms, a major peak corresponding to malvidin-3-O-glucoside was observed. Also, the in vitro antifungal activity of these extracts against mycelia growth of the phytopathogenic fungus Botrytis cinerea was evaluated. The anthocyanin containing extract from Cabernet Sauvignon grape pomace of Misiones de Rengo vineyard was the most active. The extract from the same variety form Miguel Torres vineyard did not inhibit mycelia growth of B. cinerea. In general, the other extracts were less active against the fungus.